Evaluation of Changes in Speech Production Induced by Conventional and Level-Dependent Hearing Protectors and Noise Characteristics - Vaziri, Ghazaleh (Université d'Ottawa / University of Ottawa, 2018)
The use of personal hearing protection devices (HPDs) is often recommended to protect workers' hearing from noise-induced damage when no other means of reducing noise levels at the source is effective. The effects of HPDs on speech communication cannot be neglected in spite of their benefit in reducing the risk of hearing loss. While much research has been directed at speech perception, much less is known on how HPDs affect speech production. The tendency of talkers to raise their vocal effort in noise, known as the Lombard effect, is often disrupted by HPDs due to their occlusion effect and the lower noise at the ears as well as the attenuated feedback from one’s own voice. Three main knowledge gaps are addressed in this thesis. The first gap is to characterize speech produced by talkers with or without HPDs under realistic acoustic conditions while immersed in an external noise field. The second gap is to evaluate more comprehensively speech production under protected and unprotected talker and listener ear conditions in different types of fluctuating and continous noises. The third gap is to assess the alterations in the characteristics of speech produced by talkers wearing level-dependent HPDs set at different transmission gain settings and in comparison with passive HPDs. This thesis extends methods used to recover Lombard speech elicited in an external noise field. For this purpose, two noise suppression methods, direct waveform subtraction (DWS) and adaptive noise cancellation (ANC), were found to adequately remove noise from speech recorded for SNRs as low as −10 dB. Moreover, this work contributes new knowledge on the effects of conventional passive HPDs on speech production. When talker wears HPD in noise then speech level were found to decrease by up to 9 dB in continuous noises and by 7 dB in fluctuating noises compared to open ears, while speech levels were found to increase by about 5 dB in all noises when the listener wears HPD. Furthermore, changes in pitch and spectral levels were consistent with changes in speech levels. The effects of level-dependent HPD on speech production, depending on the chosen transmission gain setting, revealed that it led to smaller decrease in talkers’ speech levels in noise compared to conventional passive HPD. These findings indicate that the level-dependent HPDs may impede communication less than conventional passive HPDs, while providing protection against high levels of noise.
Keywords: Lombard effect; External noise field; Noise suppression; Passive and level-dependent hearing protection devices; Speech production in noise